Design and Engineering of a Target for X-Ray Thomson Scattering Measurements on Matter at Extreme Densities and Gigabar Pressures. (1st September 2016) - Boehm, K.-J.; Hash, N.; Barker, D.; Döppner, T.; Farrell, M. P.; Fitzsimmons, P.; Kaczala, D.; Kraus, D.; Maranville, B.; Mauldin, M.; Neumayer, P.; Segraves, K.
Abstract: Reconciling the experimental and system requirements during the development of a new target system is one of the most challenging tasks in the design and engineering of targets used in the National Ignition Facility. Targets for the GigaBar 3 campaign were meant to allow the detection of extremely weak Thomson scattering from matter at extreme densities in the face of very bright backlighter and laser entry hole plasma emissions. The problem was to shield the detector sufficiently while maintaining beamline and view clearances, and observing target mass restrictions. A new construction process, based on a rapid prototype frame structure, was used to develop this target. Details of the design process for these targets are described, and lessons from this development for production and target assembly teams are discussed.